Strategi Humas Kantor Kementerian Agama Kota Palembang Melalui Media Online Youtube - Achmad Syarifudin; Muhammad Randicha Hamandia; Jeniedya Jeniedya (CV. ITTC INDONESIA, 2023)
This study is entitled (Public Relations Strategy for the Office of the Ministry of Religion in Palembang through Online Media Youtube), which aims to find out the strategy carried out by the public relations team in disseminating news via YouTube. In addition, it will also explain how the obstacles or obstacles faced by the public relations team of the Palembang City Ministry of Religion Office in disseminating information via YouTube. Public Relations has an important role in agencies to enhance the company's image. In addition, public relations must also work on how to establish good relations with the media. The Palembang City Ministry of Religion office plays an important role in informing the public about religious news. Dissemination of information carried out by the Public Relations Office of the Ministry of Religion of Palembang City through YouTube media. The research method used is a qualitative research approach with data collection techniques namely through interviews, observation, and documentation. As for data analysis using descriptive. The conclusion is that the online media YouTube plays a very important role in disseminating information, where the online media YouTube is very easy to access so that it becomes the right medium for disseminating information to the public.